2014
DOI: 10.3390/molecules20010001
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Polymerization of Cyclic Monomers in Ionic Liquids as a Prospective Synthesis Method for Polyesters Used in Drug Delivery Systems

Abstract: Biodegradable or bioresorbable polymers are commonly used in various pharmaceutical fields (e.g., as drug delivery systems, therapeutic systems or macromolecular drug conjugates). Polyesters are an important class of polymers widely utilized in pharmacy due to their biodegradability and biocompatibility features. In recent years, there has been increased interest in enzyme-catalyzed ring-opening polymerization (e-ROP) of cyclic esters as an alternative method of preparation of biodegradable or bioresorbable po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 131 publications
0
34
0
Order By: Relevance
“…Similarly, mutations in AIPL1 are already known to be implicated in both ar LCA and ad CRD [72]. A recent study identified two homozygous mutations in AIPL1 (c.773G>C (p.R258P) and c.465G>T (p.(H93_Q155del)) in two Pakistani families, which co-segregated with disease phenotype that could correspond to ar LCA or ar RP [73]. In 1 patient of our cohort, 2 novel likely pathogenic mutations were identified in exon 5 of AIPL1 (het c.769C>T p.(L257F) + het c.767T>G p.(I256S)), one carried by the unaffected father and one by the unaffected mother.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, mutations in AIPL1 are already known to be implicated in both ar LCA and ad CRD [72]. A recent study identified two homozygous mutations in AIPL1 (c.773G>C (p.R258P) and c.465G>T (p.(H93_Q155del)) in two Pakistani families, which co-segregated with disease phenotype that could correspond to ar LCA or ar RP [73]. In 1 patient of our cohort, 2 novel likely pathogenic mutations were identified in exon 5 of AIPL1 (het c.769C>T p.(L257F) + het c.767T>G p.(I256S)), one carried by the unaffected father and one by the unaffected mother.…”
Section: Discussionmentioning
confidence: 99%
“…Biodegradable polymeric nanoparticles, which are capable of achieving a variety of sustained release profiles of active substances with unique pharmacokinetics, offer great potential as delivery vehicles. [123] The release of AMPs from the polymeric carriers is controlled by several concurrent mechanisms: diffusion through the nanosphere matrix or nanocapsule polymer wall, erosion of the matrices or by osmotic pressure, which means that the process is very complex. [121] To date, many methods have been developed for the preparation of polymeric nanoparticles (emulsion or interfacial | 1087 PIOTROWSKA eT Al.…”
Section: Polymer-based Ddsmentioning
confidence: 99%
“…The use of enzymes (mainly lipases) in ROP reactions of lactides and other lactones has been actively pursued in organic solvents . When solvents are used in the synthesis of these polyesters, the common organic solvents are toluene and heptane, which are hazardous, toxic and flammable; lactides are poorly soluble in common organic solvents while melted lactides at high temperatures are polar/hydrophilic and inhibitory to the enzymatic propagation . In addition, lipases typically show moderate activities in these media, especially towards l ‐lactide and dl ‐lactide .…”
Section: Enzymatic Rop In Organic Solventsmentioning
confidence: 99%
“…These biodegradable polyesters are thermoplastic, and biocompatible polymers with mechanical properties similar to those of polystyrene or polyethylene terephthalate (PET or PETE) . In addition to their uses in packaging and horticultural materials, polyesters (with an average molecular weight > 60 000 g mol ‐1 ) have advantageous applications in biomedical fields (due to their high biocompatibility and lack of toxicity) including controlled drug delivery carriers (such as for Camptothecin, Doxorubicin, Amphotericin B, and Vancomycin, etc., and for therapeutic peptides/proteins and for gene delivery), tissue engineering scaffolds, surgical suture and bone fixation materials . Aliphatic polyesters can be synthesized by two common methods, i.e.…”
Section: Introductionmentioning
confidence: 99%